The Romantic Lecture in an Age of Paper (Money): Jean Paul’s Literary Aesthetics across Print and Orality - Franzel, Sean (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2010)
This article examines Jean Paul's partially fictionalized "Leipzig" lectures at the end of his Vorschule der Aesthetik, asking as to how Jean Paul reflects on literary criticism’s movement across print and oral forms of presentation. Situating the Vorschule against the backdrop of Romantic cultures of scholarly lecturing, I argue that Jean Paul expressly highlights the mediality of literary and critical language, and I discuss the applicability of recent media theoretical concepts of remediation and intermediality to the phenomenon of the Romantic lecture.